Vertebrates : - Kardong, Kenneth V. (McGraw-Hill Higher Education, 2009)
An extraordinary wealth of new information continues to enrich and enliven the discipline of vertebrate biology. This includes diverse information from molecular biology, hox genes and genomes, evolution and development, biomechanics, experimental physiology, to astonishing new fossils.